2021
DOI: 10.1002/asia.202100718
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Reduction of CO2to CO on Ag/SnO2by a Synergistic Effect of Morphology and Structural Defects

Abstract: Silver (Ag)‐based materials are considered to be promising materials for electrochemical reduction of CO2 to produce CO, but the selectivity and efficiency of traditional polycrystalline Ag materials are insufficient; there still exists a great challenge to explore novel modified Ag based materials. Herein, a nanocomposite of Ag and SnO2 (Ag/SnO2) for efficient reduction of CO2 to CO is reported. HRTEM and XRD patterns clearly demonstrated the lattice destruction of Ag and the amorphous SnO2 in the Ag/SnO2 nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Inspired by the interface characteristics, Geng and co-workers have prepared Ag/SnO 2 nanocomposites, containing the lattice destruction of Ag NPs and amorphous SnO 2 . [73] The Ag/SnO 2 nanocomposites containing 15% SnO 2 possess the highest FE CO of 99.2% at À 0.9 V (vs. RHE), and the value of FE CO is more than 90% at a wide potential range from À 0.8 V to À 1.4 V, suggesting superior selectivity. In addition, the experimental characterization and analysis have shown that amorphous SnO 2 can anchor the defect sites and inhibiting the HER.…”
Section: Ag/metal Oxides Compositesmentioning
confidence: 92%
“…Inspired by the interface characteristics, Geng and co-workers have prepared Ag/SnO 2 nanocomposites, containing the lattice destruction of Ag NPs and amorphous SnO 2 . [73] The Ag/SnO 2 nanocomposites containing 15% SnO 2 possess the highest FE CO of 99.2% at À 0.9 V (vs. RHE), and the value of FE CO is more than 90% at a wide potential range from À 0.8 V to À 1.4 V, suggesting superior selectivity. In addition, the experimental characterization and analysis have shown that amorphous SnO 2 can anchor the defect sites and inhibiting the HER.…”
Section: Ag/metal Oxides Compositesmentioning
confidence: 92%
“…Solid products were collected by centrifugation at 5000 r for 3 min, dry it in a 60 °C vacuum drying oven for 12 h and seal it for storage. For the synthesis of Ag 99 Cu 1 sample, 170 mg AgNO Electrochemical Test: According to the authors' previous test method, [53] briefly, the electrochemical experiments were carried out in H-cell with a Nafion 115 membrane as the separator. Each compartment contains 40 mL of 0.1 m KHCO 3 electrolyte (pH = 6.8).…”
Section: Methodsmentioning
confidence: 99%
“…According to the authors’ previous test method, [ 53 ] briefly, the electrochemical experiments were carried out in H‐cell with a Nafion 115 membrane as the separator. Each compartment contains 40 mL of 0.1 m KHCO 3 electrolyte (pH = 6.8).…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Up to now, massive endeavors have been devoted to designing high-performance catalysts with Au, 5,6 Ag, 7,8 and Pd 9,10 as active sites for CO 2 -to-CO transformation. Further studies have demonstrated that the adjustment of the coordination number of the active sites and the local electronic structure through crystal facets, 11 grain boundaries, 12,13 and defects 14,15 at the nanoscale and the regulation of mass transfer of substrates and electrochemically active surface area through the particle size, 16,17 morphology, 7,18 and porosity 19,20 at the mesoscale greatly influence the catalytic activity and selectivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electrochemical reduction reaction of CO 2 (CO 2 RR) is an ideal solution to alleviate the greenhouse effect among different CO 2 fixation methods for its high environmental compatibility. , Among various CO 2 RR pathways, electrochemical CO 2 reduction to CO is considered one of the most promising approaches due to its considerable technical and economic feasibility. , Up to now, massive endeavors have been devoted to designing high-performance catalysts with Au, , Ag, , and Pd , as active sites for CO 2 -to-CO transformation. Further studies have demonstrated that the adjustment of the coordination number of the active sites and the local electronic structure through crystal facets, grain boundaries, , and defects , at the nanoscale and the regulation of mass transfer of substrates and electrochemically active surface area through the particle size, , morphology, , and porosity , at the mesoscale greatly influence the catalytic activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%